2018
DOI: 10.1021/acscatal.8b03661
|View full text |Cite
|
Sign up to set email alerts
|

A Copper-Peptoid as a Highly Stable, Efficient, and Reusable Homogeneous Water Oxidation Electrocatalyst

Abstract: Water electrolysis is among the simplest methods to generate hydrogen, which can be used as a clean and renewable energy source. Within this process, the oxidation of water into molecular oxygen is considered as the bottleneck reaction because it involves the transfer of four electrons toward the oxidation of a highly stable small molecule. Challenges in this area include the development of stable and effective electro-and photocatalysts that utilize readily available metal ions. Herein we report a copper− pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 64 publications
3
45
0
Order By: Relevance
“…B, H‐Nphen‐NTEMPO‐Npm‐NH 2 peptoid trimer used for copper‐mediated alcohol oxidations and imine synthesis . C, H‐Npm‐Nhe‐Nhe(bipy)‐NH 2 peptoid trimer employed as a copper‐centred catalyst for water oxidation…”
Section: Peptoids As Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…B, H‐Nphen‐NTEMPO‐Npm‐NH 2 peptoid trimer used for copper‐mediated alcohol oxidations and imine synthesis . C, H‐Npm‐Nhe‐Nhe(bipy)‐NH 2 peptoid trimer employed as a copper‐centred catalyst for water oxidation…”
Section: Peptoids As Catalystsmentioning
confidence: 99%
“…Ghosh et al . used a similar peptoid trimer format, H‐Npm‐Nhe‐Nhe(bipy)‐NH 2 (Figure C), to reveal a copper(II/III) homogeneous electro‐catalyst for water oxidation.…”
Section: Peptoids As Catalystsmentioning
confidence: 99%
“…Peptoids, N‐substituted glycine oligomers, are an important class of peptidomimetic foldamers, with demonstrated utilities such as metal binding and solution catalysis . Peptoids can be efficiently generated on resin by a solid‐phase method (the “submonomer method”, Figure ) from various primary amines, with high sequence specificity, and are chemically inert towards many catalytic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these features, we have recently designed and developed a unique bio‐inspired oxidation catalyst, BT , which incorporates two catalytic side‐chains, phenanthroline‐copper and 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO), and one non‐catalytic benzyl group. [7b], [7c] We showed that BT , combined with Cu I and N ‐methyl imidazole (NMI) in an acetonitrile solution, performs in the oxidation of benzylic, allylic and aliphatic primary alcohols with turn‐over‐frequency (TON) of up to 490 (at 0.1 mol‐% catalyst). This TON is 16 times higher than the TON obtained when a mixture of the two catalytic groups, or the peptoid dimer ( DI ) that is lacking the non‐catalytic group were used in the same reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation